2017
DOI: 10.1371/journal.pone.0184989
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic determinants of smoking among Iraqi adults: Data from Non-Communicable Risk Factor STEPS survey 2015

Abstract: AimHighlight the socio-economic determinants of smoking among Iraqi adults aged (18+) years.MethodThe study is derived from Non-Communicable Diseases Risk Factors STEPS survey Iraq 2015. A cross-sectional survey conducted among households from 15 Iraqi governorates. Nainawa, Salahaddin and Al-Anbar were excluded for unstable conditions. Multi-stage cluster sampling technique used to include 4120 Iraqi adults. Interviews started from the first week of November for 20 days using Arabic and Kurdish translated ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
3
11
2
Order By: Relevance
“…A lower basic education was associated with daily smoking in Russian, and general population men, and unemployment among Kurdish and general population men. Our results on the association of daily smoking and educational level were in line to previous findings from Iraq [ 32 ]. An unsatisfactory economic situation was associated with daily smoking among Somali and Kurdish men.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A lower basic education was associated with daily smoking in Russian, and general population men, and unemployment among Kurdish and general population men. Our results on the association of daily smoking and educational level were in line to previous findings from Iraq [ 32 ]. An unsatisfactory economic situation was associated with daily smoking among Somali and Kurdish men.…”
Section: Discussionsupporting
confidence: 92%
“…Specific information about the prevalence rates of alcohol use and smoking in the Kurdistan area or among Kurdish migrants is very limited, but the prevalence of lifetime abstainers from alcohol in Iran and Iraq has been reported to be high [ 28 , 29 ]. The prevalence of daily smoking is similar or higher in men in Eastern Mediterranean Region compared with European countries but much lower in women [ 1 , 26 , 27 , 30 32 ]. However, there are also contradictory findings reporting lower rates of daily smoking in Iran and Iraq compared to the European general estimates [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…A national-level study from Saudi Arabia reported no significant differences in smoking prevalence by education level (Moradi-Lakeh et al 2015 ). Employment relationship with smoking prevalence was not significant according to Memon et al ( 2000 ) study in Kuwait as well in other studies (Al-Badri et al 2017 ; Bang and Kim 2001 ; Sheridan et al 2018 ). Single and married participants had the highest smoking prevalence compared with other marital status in this study.…”
Section: Discussionmentioning
confidence: 69%
“…However, this is not the case in several other countries: Mexico and China have lower smoking rates among the poor [ 34 ]. In a study of Iraqi adults, per capita monthly income was not significantly associated with smoking status [ 37 ]. Schaap et al .…”
Section: Discussionmentioning
confidence: 99%